Kajian Konsep Arsitektur Maskulin Pada Bangunan Museum Guggenheim, Bilbao - Priambudi Dwi Prasetyo; Ari Widyati Purwantiasning (Program Sarjana Arsitektur Universitas Internasional Batam, 2021)
Architecture is closely related to masculine traits due to the intervention of experts in the modern era. Existence became greatly reduced because of the feminism movement in architecture that had taken the attention of activists of architectural practice. Therefore, to bring back insights on the concept of masculine architecture, this research was conducted. In this study, qualitative descriptives were used as a method, as was the concept of masculine architecture that was not expected to be measured through quantitative data. In this method is very focused on the literature data due to the current conditions that can not make a direct visit to the site of the case study. The preferred case study is the Guggenheim museum in Bilbao, Spain. In data collection of course refers to the principles of masculine architecture. These principles include natural impressions on elements, color selection, industrial-style ornaments, and the use of steel materials. Some of these principles are further identified in the architectural elements that are considered capable of displaying a masculine architectural impression on this Guggenheim museum building. The result of this identification proves that every principle of masculine architecture is able to be presented very well to the building elements of this Guggenheim museum. In addition, we also find about the implementation strategy that is considered optimal to bring the impression of masculine architecture to a museum building, while still presenting something innovative but still has its own characteristics.